Jacob Neusner a studium rabínské literatury formativního období = Jacob Neusner and the study of Rabbinic literature of the formative period - Sládek, Pavel (Religio, 2017)
Jacob Neusner (1932-2016) was among the few academics in the field of Jewish Studies whose renown and impact reached beyond the academic domain and who was generally regarded by the wider public as a leading Jewish scholar. However, Neusner's reputation within the discipline was and remains rather ambiguous. This article delineates the apparent flaws in Neusner's many works but also argues that such criticism should not blind us to the groundbreaking methodological innovations introduced by Neusner to the study of Rabbinic literature of the formative period. His cavalier approach to philological work renders not only his translations of Rabbinic texts but also many details in his original works unreliable, because they are based solely on those same translations. On the other hand, Neusner's frontal attack on the uncritical circular construction of the history of the Rabbinic movement and its literary output from those same texts, mistakenly read as historical sources, opened a new era in the academic study of early Rabbinic Judaism. On the basis of admitting that all extant texts emerged from within the Rabbinic movement and represent its proponents' ideology and self-perception, Neusner called for research questions to be limited only to those that were congruent with the nature of the available texts, even if certain questions would remain unanswered. Equally, Neusner's plea for a structural approach to classical Rabbinic texts, regarding them as composite documents resulting from anonymous and collective redactions, opened new vistas and inspired analytical research methods that would have been unthinkable without Neusner, even though he paradoxically rejected their results whenever they contradicted his own views.